BQ-AurIPr: a redox-active anticancer Au(i) complex that induces immunogenic cell death - Mule, Ravindra D.; Kumar, Akhilesh; Sancheti, Shashank P.; Senthilkumar, B.; Kumar, Himanshu; Patil, Nitin T. (Chemical Science, 2022)
Immunogenic Cell Death (ICD) is a unique cell death mechanism that kills cancer cells while rejuvenating the anticancer immunosurveillance, thereby benefiting the clinical outcomes of various immuno-chemotherapeutic regimens. Herein, we report development of a library of benzo[a]quinolizinium-based Au(i) complexes through an intramolecular amino-auration reaction of pyridino-alkynes. We tested 40 candidates and successfully identified BQ-AurIPr as a novel redox-active Au(i) complex with potent anticancer properties. BQ-AurIPr efficiently triggered generation of DAMPs - the hallmarks of ICD - and was superior in terms of efficiency compared to FDA-approved drugs known to induce ICD. BQ-AurIPr significantly increased immunogenicity of cancer cells enhancing their phagocytosis when co-cultured with immune cells. Our investigation reveals that BQ-AurIPr induces oxidative stress inside mitochondria leading to mitophagy, as the mechanism for immunogenic cell death in A549 cells.